Particularisme juridique et développements communs (Moyen-Âge–Temps modernes): Une perspective suédoise - Mia Korpiola (Institute for Social, Political and Legal Studies (Valencia, Spain), 2022)
This article discusses some key features of the medieval and early modern Swedish legal culture from a comparative European perspective. These key traits include an early codification of (nation-wide) law, the predominance of written law and a reliance on laymen as judges rather than university-trained lawyers. In fact, these became cornerstones of a national legal historical identity in early modern and modern Sweden and Finland. Finally, a comparative approach is considered indispensable in order to analyse particularisms and common developments in legal history.